2011
DOI: 10.2337/db11-0197
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-Like Growth Factor-1 Receptor Is a Negative Regulator of Nitric Oxide Bioavailability and Insulin Sensitivity in the Endothelium

Abstract: OBJECTIVEIn mice, haploinsufficiency of the IGF-1 receptor (IGF-1R+/−), at a whole-body level, increases resistance to inflammation and oxidative stress, but the underlying mechanisms are unclear. We hypothesized that by forming insulin-resistant heterodimers composed of one IGF-1Rαβ and one insulin receptor (IR), IRαβ complex in endothelial cells (ECs), IGF-1R reduces free IR, which reduces EC insulin sensitivity and generation of the antioxidant/anti-inflammatory signaling radical nitric oxide (NO).RESEARCH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 54 publications
11
83
0
Order By: Relevance
“…As the IR was also found to be phosphorylated by IGF1 using western blot, we interpret this observation as an effect of insulin/IGF1 hybrid receptors where IGF1 binding to the IGF1R ab-dimer transphosphorylates the IR b-subunit (Ward et al 2007). This corroborates with the findings of Abbas et al (2011) who showed that reduction in the expression of IGF1R by siRNA, thus reducing the number of insulin/IGF1 hybrid receptors, increased the response to insulin in HUVECs.…”
Section: Discussionsupporting
confidence: 90%
“…As the IR was also found to be phosphorylated by IGF1 using western blot, we interpret this observation as an effect of insulin/IGF1 hybrid receptors where IGF1 binding to the IGF1R ab-dimer transphosphorylates the IR b-subunit (Ward et al 2007). This corroborates with the findings of Abbas et al (2011) who showed that reduction in the expression of IGF1R by siRNA, thus reducing the number of insulin/IGF1 hybrid receptors, increased the response to insulin in HUVECs.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, hyperinsulinemia stimulates theca-cell receptors via IGF-1 and causes ovarian hyperandrogenemia (22). Furthermore, in a recent study the IGF-1 receptor was found to play a critical negative regulator role in insulin sensitivity (23). Likewise, in the present study, IGF-1 levels were found to be higher in patients with insulin resistance.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, endothelial cells have more IGF1 receptors than insulin receptors. Haploinsufficient Igf1r C/K mice had decreased IGF1 receptors, enhanced insulin-mediated glucose disposal, restored insulin-mediated aortic vasorelaxation, and increased insulin-stimulated endothelial cell NO release (Abbas et al 2011). Haploinsufficient Igf1r C/K mice also had fewer angiogenic progenitor cells than WT mice, but these cells had increased adhesion to fibronectin, increased IGF1 secretion and enhanced tube formation (Yuldasheva et al 2014).…”
Section: Igfs and Atherosclerosismentioning
confidence: 98%